Development of a real-time TaqMan PCR assay for the detection of porcine circovirus 4 - Chen Wanting; Jiang Dike; Xiao Lu; Zhang Pengfei; Luo Yan; Yang Zexiao; Yao Xueping; Wang Yin; Wu Xulong (Journal of Veterinary Research, 2022)
Porcine circovirus 4 (PCV4) was first discovered in 2019 in a herd of pigs with porcine respiratory disease, dermatitis and nephropathy syndrome in Hunan Province, China. It has subsequently been detected in other provinces and in South Korea. In consideration of the potential of the virus to cause an epidemic, rapid, sensitive, and specific detection of PCV4 is needed, as is the facilitation of further epidemiological research through elucidation of the whole genome of PCV4. This study had those two aims.